Quaternary chronostratigraphy and stable isotope paleoecology of Big Bone Lick, Kentucky, USA. Issue 3 (May 2015) - Tankersley, Kenneth Barnett; Murari, Madhav Krishna; Crowley, Brooke E.; Owen, Lewis A.; Storrs, Glenn W.; Mortensen, Litsa
Abstract : Big Bone Lick (BBL) in northern Kentucky, USA has been a critical geologic site in the historical development of North American Quaternary vertebrate paleontology since the 1700s. Sedimentology, geoarcheology, paleontology, accelerator mass spectrometry radiocarbon and optically stimulated luminescence dating, and stable carbon and nitrogen isotope analyses were undertaken to develop a chronostratigraphy and history of erosion and deposition for the site to provide a foundation for understanding taphonomy, and species extinction and adaptation to periods of climatic and environmental change. Three geomorphic surfaces are recognized at BBL representing significant periods of floodplain aggradation since the last glacial maximum (26.5–19 ka) dating to the Oldest Dryas (Tazewell, 25–19 ka), the Older Dryas (Cary, 14–12 ka), and late Holocene (5 ka to the present). Unconformities suggest significant periods of degradation during the transitions from cold and dry to warm and moist climates from the Oldest Dryas (Tazewell) to Bølling Oscillation, from the Older Dryas (Cary) to the Allerød, and from the Younger Dryas (Valders) to the Holocene Climatic Optimum. Increased anthropogenic activities since ~ 5 ka may have increased soil upland erosion and floodplain aggradation. Stable isotopes demonstrate that the landscape has been dominated by C3 vegetation since the last glacial maximum.